KEWENANGAN DEWAN PEMBINA DAN PENGENDALI PENGELOLAAN KOLABOATIF (DP3K) TAMAN NASIONAL KAYAN MENTARANG (TNKM) NASIONAL KAYAN MENTARANG (TNKM) - Gunawan, Muhammad (Universitas Borneo Tarakan, 2017)
Abstract KMNP (Taman Nasional Kayan Mentarang) collaborative management essentially an innovation in the management of National Parks in Indonesia that promote mutual interests, shared responsibility, the role and benefits between government, local communities and NGOs. In this paper, the issue raised is the authority of the Dewan Pembina dan Pengendali Pengelolaan Kolaboratif (DP3K) KMNP. The aim of this study was to determine and analyze the authority of the Board of Trustees and Collaborative Management Controller (DP3K) Kayan. This type of research is the study of normative juridical approach to legislation and conceptual approach and the use of primary and secondary law with a qualitative analysis approach. Based on the results, the conclusion that the authority DP3K TNKM among others embodies the aspirations of the parties in order to develop and control the implementation of collaborative management KMNP.Keywords: National Parks, collaborative management, Authority.